Experimental investigation of Jalousie type window frames subjected to static wind pressure - Acosta, Timothy John; Carandang, Alvin Junor
Glazing components of a building envelope refer to windows, doors, or any portions made of glass that permit light and provide an outside view of a building. However, in the presence of severe winds, glazing components are prone to failure. This study experimentally investigated the capacity of typical jalousie type window frames against simulated static wind pressures. The static wind pressures were simulated inside an air chamber to create a pressure difference across samples. In this study, five large-scale tests were performed where four of which experienced pull-through failures of the standard aluminum casing and one of which experienced breakage of glass blades. A four-point bending test was also done to measure the capacity of the glass subjected to uniform pressure. It was observed that the governing mode of failure for the window system was the pull-through failure at a mean pressure capacity of 4.218 kPa with a coefficient of variance of 0.23. The capacity of the glass was observed to fail at a higher mean pressure of 6.508 kPa with a coefficient of variance of 0.25. The threshold capacity obtained from this study will be useful for developing fragility curves of buildings in future studies.
Keywords: Jalousie; Window frame; Static wind pressure